CHEMICAL COMPOSITION, ANTIMICROBIAL AND ANTIOXIDANT ACTIVITY OF THE ESSENTIAL OIL OF CRITHMUM MARITIMUM L. - A. ÇELİK; E. N. HERKEN; A. ERMİŞ; O. KAYGUSUZ; Samire AYDEMİR (International Journal of Secondary Metabolite)
In this study, the chemical constituents, antioxidant and antimicrobial activity of the essential oil of the plant species of Crithmum maritimum L. were evaluated. The essential oil was obtained by hydrodistillation method using a Clevenger-type apparatus. The constituents were analyzed by gas chromatography/mass spectroscopy (GC/MS). The major components of the essential oil were detected as γ terpinene (42.95 %), β- phellandrene (25.03 %). Total phenolic compounds were analyzed by Folin-Ciocalteu reagent method and found as 28.48 g gallic acid equivalent/g. Antioxidant capacity of essential oil was tested by using Trolox Equivalent Antioxidant Capacity (TEAC) assay in vitro, and total antioxidant capacity was found as 9.18 mg TE/g. The antibiotic assay of the essential oil on twelve pathogenic bacteria including Staphlococcus chromonogenes ATCC 43764, Staphlococcus xylosus ATCC 29971, Staphlococcus warneri ATCC 29971, Staphlococcus hominis ATCC 27844, Staphlococcus aureus PSC 18, Listeria monocytogenes ATCC 7644, Salmonella typhimurium ATCC 74028, Proteus vulgaris NRRL-B 123, Bacillus cereus ATCC 11778, Bacillus subtilis, Enterococcus fecalis ATCC 19433, Pseudomonas aurageniosa ATCC 27853 was examined with agar disc diffusion method and antimicrobial activity of the oil was evaluated to be high.